Interdependence and Intersubjectivity: Spinoza on Recognition - Martin Saar (Journal of Spinoza Studies, 2025)
The modern concept “recognition” has no systematic place in Spinoza’s early modern system, but he has interesting things to say about many of the dimensions and activities that fall under that term. To start somewhere, I use a recent conceptualization of different types of recognition theory to trace these elements in Spinoza's works and construct the outlines of his quasi-theory of recognition. Playing out differently in the registers of the epistemic, the affective and the moral, Spinozian recognition seems less oriented towards an identity to be recognized than towards the very dynamic and becoming inherent in all social relationships.